2013
DOI: 10.1186/1471-2334-13-57
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in patients hospitalized with pandemic influenza A(H1N1)pdm09 virus infection–United States, 2009

Abstract: BackgroundAsthma was the most common co-morbidity among patients hospitalized with pandemic influenza A(H1N1)pdm09 [pH1N1] infection. The objective was to compare characteristics of hospitalized pH1N1 patients with and without asthma and assess factors associated with severity among asthma patients.MethodsPatient data were derived from two 2009 pandemic case-series of U.S. pH1N1 hospitalizations. A case was defined as a person ≥ 2 years old hospitalized with laboratory-confirmed pH1N1. Asthma status was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 19 publications
3
35
0
Order By: Relevance
“…These results are consistent with previous studies reporting that one-third of the patients in the United States hospitalized with influenza had asthma [15]. In addition, a recent study by McKenna et al reported an overlap in asthma and chronic obstructive pulmonary disease (COPD) in over 20% of the 50-64-years and 65-years-and-older age groups [15]. However, because these patients are not regularly monitored by spirometer, it is difficult to determine whether they had asthma, COPD, or both asthma and COPD [16].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous studies reporting that one-third of the patients in the United States hospitalized with influenza had asthma [15]. In addition, a recent study by McKenna et al reported an overlap in asthma and chronic obstructive pulmonary disease (COPD) in over 20% of the 50-64-years and 65-years-and-older age groups [15]. However, because these patients are not regularly monitored by spirometer, it is difficult to determine whether they had asthma, COPD, or both asthma and COPD [16].…”
Section: Discussionsupporting
confidence: 93%
“…This high rate in CF patients compared to the general population (hospitalization rate 7–20%) should be interpreted with caution, though [13]. For medical staff confronted with CF patients experiencing a H1N1 infection, the need for hospitalization was difficult to estimate at the beginning of the pandemic phase due to lack of experience with the clinical course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma, a complicated disease involving multiple intrinsic and extrinsic parameters, is a major underlying condition associated with respiratory infections. Clear clinical and epidemiological data demonstrate that asthmatics are at high risk of hospitalization during influenza epidemics; however, recent studies show that asthmatics were less likely to die from pH1N1 and suffer less severe symptoms and outcomes once hospitalized 3 , 4 , 5 , 7 , 8 , 9 . As the existing models typically utilize influenza viruses as initiators or exacerbators of asthma in mice, 17 , 18 the question of how the asthmatic hosts’ immune response to influenza differs from that of the normal host has not been previously addressed.…”
Section: Discussionmentioning
confidence: 99%